Boundary-crossing careers and the 'third space of hybridity': Career actors as knowledge brokers between creative arts and academia. (November 2018) - Lam, Alice
This article examines how boundary-crossing careers influence creative knowledge combination by looking at a group of creative artists whose careers straddle professional arts and academia. Whereas previous research has treated individuals as vehicles for knowledge transmission across intertwined networks, this study emphasizes their active role as knowledge brokers. It examines how work role transitions trigger a dynamic interplay between actors and contexts, and brings about changes in the cognitive frames of individuals and their propensity to connect knowledge across contexts. The study employs Bhabha's concept of the 'third space of hybridity' to denote the agency space where career actors construct hybrid role identities and engage in knowledge brokering. The analysis identifies two categories of hybrid with different boundary-crossing careers and shows how work role transitions influence the topology of the third space where knowledge brokering occurs. The 'artist-academics' whose careers span art and academia concurrently experience recurrent micro-role transitions. They are 'organic' hybrids operating at the 'overlapping space' where knowledge translation and integration occur naturally in everyday work. They are 'embedded' knowledge brokers. The 'artists-in-academia', who cross over from the art world to academia, experience more permanent macro-role transitions. They are 'intentional hybrids' who make conscious efforts to bridge two discrete work domains by creating a separate 'transitional space'. Their knowledge brokering activities are instrumental in transforming both their own knowledge and that of their work context: they are transformative knowledge brokers. The study advances our understanding of career mobility as a mechanism that facilitates creative knowledge combination by highlighting actor agency and the underlying cognitive-behavioural mechanisms.